From one species to another: A review on the interaction between chemistry and microbiology in relation to cleaning in the built environment. (6th September 2019) - Velazquez, Samantha; Griffiths, Willem; Dietz, Leslie; Horve, Patrick; Nunez, Susie; Hu, Jinglin; Shen, Jiaxian; Fretz, Mark; Bi, Chenyang; Xu, Ying; Van Den Wymelenberg, Kevin G.; Hartmann, Erica M.; et al.
Abstract: Since the advent of soap, personal hygiene practices have revolved around removal, sterilization, and disinfection—both of visible soil and microscopic organisms—for a myriad of cultural, aesthetic, or health‐related reasons. Cleaning methods and products vary widely in their recommended use, effectiveness, risk to users or building occupants, environmental sustainability, and ecological impact. Advancements in science and technology have facilitated in‐depth analyses of the indoor microbiome, and studies in this field suggest that the traditional "scorched‐earth cleaning" mentality—that surfaces must be completely sterilized and prevent microbial establishment—may contribute to long‐term human health consequences. Moreover, the materials, products, activities, and microbial communities indoors all contribute to, or remove, chemical species to the indoor environment. This review examines the effects of cleaning with respect to the interaction of chemistry, indoor microbiology, and human health.